2012
DOI: 10.1016/j.dcn.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of the left intraparietal sulcus in the relationship between symbolic number processing and children's arithmetic competence

Abstract: The neural foundations of arithmetic learning are not well understood. While behavioral studies have revealed relationships between symbolic number processing and individual differences in children's arithmetic performance, the neurocognitive mechanisms that bind symbolic number processing and arithmetic are unknown. The current fMRI study investigated the relationship between children's brain activation during symbolic number comparison (Arabic digits) and individual differences in arithmetic fluency. A signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
1
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 33 publications
12
81
1
7
Order By: Relevance
“…Previous research has yielded a variety of findings with regards to how symbolic and non-symbolic number representation systems relate to exact calculation ability. Findings from this study were consistent with previous research indicating that both non-symbolic system acuity (Halberda et al, 2008;Libertus, Feigenson, & Halberda, 2011;Mazzocco, Feigenson, & Halberda, 2011) and symbolic system acuity (Bugden et al, 2012;Vogel, Remark, & Ansari, 2015) individually relate to exact calculation, and corroborate previous findings suggesting that when the impact of both representation systems are examined in relation to exact calculation skill, only symbolic system acuity remains a significant predictor (Holloway & Ansari, 2009;Kolkman, Kroesbergen, & Leseman, 2013;Newton, Waring, & Penner-Wilger, 2014;Sasanguie, Göbel, Moll, Smets, & Reynvoet, 2013). The nature of the relation between these two systems and exact calculation skill was examined and it was found that symbolic system performance mediates the relation between non-symbolic system performance and exact calculation skill.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has yielded a variety of findings with regards to how symbolic and non-symbolic number representation systems relate to exact calculation ability. Findings from this study were consistent with previous research indicating that both non-symbolic system acuity (Halberda et al, 2008;Libertus, Feigenson, & Halberda, 2011;Mazzocco, Feigenson, & Halberda, 2011) and symbolic system acuity (Bugden et al, 2012;Vogel, Remark, & Ansari, 2015) individually relate to exact calculation, and corroborate previous findings suggesting that when the impact of both representation systems are examined in relation to exact calculation skill, only symbolic system acuity remains a significant predictor (Holloway & Ansari, 2009;Kolkman, Kroesbergen, & Leseman, 2013;Newton, Waring, & Penner-Wilger, 2014;Sasanguie, Göbel, Moll, Smets, & Reynvoet, 2013). The nature of the relation between these two systems and exact calculation skill was examined and it was found that symbolic system performance mediates the relation between non-symbolic system performance and exact calculation skill.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, in a functional Magnetic Resonance Imaging (fMRI) study, Bugden et al (2012) demonstrated that the degree to which the left IPS is modulated by numerical ratio, during a symbolic number comparison task, is related to standardized measures of arithmetic fluency (over and above reading fluency) in 8-10 year old children. In other words, those children who exhibited a larger symbolic ratio effect on activity in the left IPS also displayed relatively stronger performance on the standardized tests of speeded arithmetic.…”
Section: Brain Imaging Datamentioning
confidence: 99%
“…While some of these researchers have indexed ANS acuity using Weber fractions (e.g. Castronovo & Gobel, 2012;Halberda et al, , 2012Inglis et al, 2011;Libertus et al, 2012;Lyons & Beilock, 2011;Piazza et al, 2010;Price et al, 2012;Sasanguie et al, 2012), others have used NREs (e.g., Bugden et al, 2012;Holloway & Ansari, 2009;Lourenco et al, 2012;Merkley & Ansari, 2010;Price et al, 2012), and others accuracy (e.g. Fuhs & McNeil, 2013;Nys et al, 2013;Wei et al, 2012).…”
Section: Price Et Al (2012) Calculated Immediate Test-retest Reliabimentioning
confidence: 99%
“…Finally, some researchers have adopted the Numerical Ratio Effect (NRE), or the closely related Numerical Distance Effect (NDE), to index ANS acuity (e.g., Bugden, Price, McLean & Ansari, 2012;Gilmore et al, 2011;Holloway & Ansari, 2009;Lonnemann, Linkersdorfer, Hasselhorn & Lindberg, 2011;Merkley & Ansari, 2010;Price et al, 2012;Sasanguie, Van den Bussche, & Reynvoet, 2012;Vanbinst, Ghesquière, & De Smedt, 2012). …”
mentioning
confidence: 99%